Risk of Developing Checkpoint Immune Pneumonitis and Its Effect on Overall Survival in Non-small Cell Lung Cancer Patients Previously Treated With Radiotherapy - Barrón, Feliciano; Sánchez, Roberto; Arroyo-Hernández, Marisol; Blanco, Carolina; Zatarain-Barrón, Zyanya L.; Catalán, Rodrigo; Ramos-Ramírez, Maritza; Cardona, Andrés F.; Flores-Estrada, Diana; Arrieta, Oscar (Frontiers in Oncology, 2020)
Introduction. Immune Checkpoint inhibitor-related Pneumonitis (ICIP) is a rare, but potentially life threatening immune-related adverse event (irAE), especially in non-small cell lung cancer (NSCLC) patients. Currently, the potential for increased irAE in patients who receive radiotherapy is scarcely known, although the connection between anti-tumor immune responses and irAEs has been suggested. In this study, we evaluated the development of ICIP in non-small cell lung cancer patients with prior radiotherapy, treated with immunotherapy in the second-line. Methods. In this retrospective trial, we included patients treated with second-line immunotherapy at the National Institute of Cancer in Mexico City from February 2015 to February 2018. Clinical, radiological and treatment variables were evaluated according to the presence of ICIP as defined by the Common Terminology Criteria for Adverse Events (4.0) in patients with or without a previous (≥months) history of radiotherapy. Results. Among 101 NSCLC patients who received treatment with ICIs, twenty-two patients (21.8%) were diagnosed with ICIP, of which 73% (n=16/22) had a history of radiotherapy (OR 6.04, 95% CI 2.03-18.0, p<0.001 in multivariate analysis). Median progression free survival and OS were similar in patients who developed ICIP compared with those who did not, however patients who presented grade ≥2 ICIP had an increased risk of mortality (HR 2.54, 95% CI 1.20-5.34, p=0.014). Conclusions. In this real-world cohort of NSCLC patients treated with ICI, the history of prior radiotherapy was associated with increased risk for ICIP development. Unlike other irAEs, grade ≥2 ICIP is an independent prognostic factor for decreased survival in NSCLC patients.